2010
DOI: 10.1016/j.poly.2010.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, EPR spectral studies and crystal structures of manganese(II) complexes of neutral N,N donor bidentate Schiff bases and azide/thiocyanate as coligand

Abstract: a b s t r a c tFour manganese(II) complexes Mn 2 (paa) 2 (N 3 ) 4 (1), [Mn(paa) / 2 H 2 O (4) of three neutral N,N donor bidentate Schiff bases were synthesized and physico-chemically characterized by means of partial elemental analyses, electronic, infrared and EPR spectral studies. Compounds 3 and 4 were obtained as single crystals suitable for X-ray diffraction. Compound 4 recrystallized as Mn(dpka) 2 (NCS) 2 . Both the compounds crystallized in the monoclinic space groups P2 1 for 3 and C2/c for 4. Manga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…The ESR spectrum for complex ( 2 ) displays isotropic spectrum accompanied with (g) value of 2.12 and two broad signals with no hyperfine structure. It was concluded that the broadness of this peak is ascribed to dipolar interaction and a random orientation of Copper(II) ion in addition to the interaction between the unpaired electron and the magnetic nuclei …”
Section: Resultssupporting
confidence: 78%
“…The ESR spectrum for complex ( 2 ) displays isotropic spectrum accompanied with (g) value of 2.12 and two broad signals with no hyperfine structure. It was concluded that the broadness of this peak is ascribed to dipolar interaction and a random orientation of Copper(II) ion in addition to the interaction between the unpaired electron and the magnetic nuclei …”
Section: Resultssupporting
confidence: 78%
“…Sharp and strong bands at 1094 cm −1 and 1100 cm −1 give evidence for the presence of ionic perchlorate in the spectra of 1 and 2 respectively . The appearance of a strong band at 2044 cm −1 in the IR spectrum of 2 indicates the presence of monodentate azide . Strong bands at 2926 cm −1 and 3451 cm −1 in the IR spectrum are assigned as alkyl C−H and N−H stretching vibrations in complex 2 respectively …”
Section: Resultsmentioning
confidence: 99%
“…A characteristic unsplit strong peak at 2049 cm −1 shown by complex 1 is attributable to asymmetric bridging nature of the azido ion . Further the symmetric stretching, ν s (N 3 ) and bending mode δ(N 3 ) of the azido group are ascertained from the peak positions at 1437 and 761 cm −1 respectively . In the case of dicyanamido complex 2 , the slight shift in frequency from that of the free dca anion [ν as + ν s (C=N) combination modes (2286 cm −1 ), ν as (C=N) (2232 cm −1 ) and ν s (C=N) (2179 cm −1 )] to 2288, 2231 and 2160 cm −1 respectively is indicative of the bridging bidentate dca .…”
Section: Resultsmentioning
confidence: 99%